2020
DOI: 10.1177/0032321720933082
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion without Solidarity: Education, Economic Security, and Attitudes toward Redistribution

Abstract: Highly educated individuals tend to be less supportive of redistribution by most accounts because they have more to lose and less to gain from it. In this article, we use European Social Survey data to develop the argument that university education reduces support for redistribution in large part independently of the improved material circumstances with which it is associated. While university encourages a range of progressive ideas related to cultural inclusivity, it simultaneously encourages conservative red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
1
27
0
2
Order By: Relevance
“…The findings confirm the role of education for individuals' position on social cleavages and add a piece to this puzzle: the education effect persists over generations, as the group of graduates with highly educated origins differ in their attitudes towards Brexit from their firstgeneration graduate peers. Thus, our findings feed into the research on the preferences and partisan identities of university graduates (Ansell & Gingrich, 2018;Gelepithis & Giani, 2020;Gingrich & Häusermann, 2015;Häusermann et al, 2015). In particular, our findings lend support to Ansell and Gingrich's (2018) expectation that heterogeneity between graduates may make it difficult to bind cross-class coalitions.…”
Section: Discussionsupporting
confidence: 80%
“…The findings confirm the role of education for individuals' position on social cleavages and add a piece to this puzzle: the education effect persists over generations, as the group of graduates with highly educated origins differ in their attitudes towards Brexit from their firstgeneration graduate peers. Thus, our findings feed into the research on the preferences and partisan identities of university graduates (Ansell & Gingrich, 2018;Gelepithis & Giani, 2020;Gingrich & Häusermann, 2015;Häusermann et al, 2015). In particular, our findings lend support to Ansell and Gingrich's (2018) expectation that heterogeneity between graduates may make it difficult to bind cross-class coalitions.…”
Section: Discussionsupporting
confidence: 80%
“…Most researchers have argued that divisions over socio‐cultural conflicts around immigration and supranational authority are responsible for the rise of an education cleavage anchored by radical right, green and liberal parties (Bornschier, 2010; Ford & Jennings, 2020, p. 300–302; Hooghe & Marks, 2018; Stubager, 2010). However, economic inequality along educational lines is as sharp as ever, stoking renewed scholarly interest in the effects of education on attitudes towards redistribution (Bullock, 2020; Gelepithis & Giani, 2020; Marshall, 2015, 2019; Mendelberg et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the Appendix, we show that the results below are highly similar if we fix the bandwidth at a range of values (0.5, 1, 3, 5, and 10) (see We include a dummy for female survey interviewer as a covariate because previous research has found that the gender of the interviewer can affect responses to gender-related survey questions (Kane and Macaulay, 1993). Education has been found to be a strong predictor of key socio-political attitudes (e.g., Hagendoorn and Nekuee, 2018;Gelepithis and Giani, 2020), including gender-related attitudes (e.g., Gök et al, 2019). 9 We also tested whether the slope of the interaction between the household education gap and the assignment varied statistically significantly by country.…”
Section: Resultsmentioning
confidence: 99%